Teacher Behavior Checklist e Implicit Relational Assessment Procedure en la evaluación docente - Neves Balan, Raquel (2022)
The evaluation of teachers has been conducted with instruments such as the Teacher Behavior Checklist (TBC), whose evidence of content validity was obtained by verbal reporting. The relationship between six TBC items and the “Good Teacher” stimulus was assessed using the IRAP, and the correlation between the score of participants in an undergraduate course and the teacher’s assessment was assessed. Forty university students participated, who answered both instruments and reported the grade received in the discipline. The D-IRAP scores’ averages were statistically significant for “good teacher-positive-true” and “bad teacher-negative-true”. The correlation indexes between the participants’ grades in the discipline and the way they evaluated the teacher were not statistically significant.